THE EFFECT OF EXPERIMENTAL MARKETING ON REVISIT INTENTION TOURISTS IN MANDEH ISLAND TOURISMN OBJECT, PESISIR SELATAN REGENCY - Vicky Brama Kumbara; M Afuan; Ramdhani Bayu Putra (Jurnal Ipteks Terapan, 2020)
The aims of this study is to analyze the influence of sense, feel, think and act on the interest of tourists visiting Mandeh Island tourism object in Pesisir Selatan Regency. This research is a type of causative research. The population in this study is the tourist in Mandeh Island tourism object. Purposive sampling was used to take a sample, there are 100 people chosen as a sample by using the William G. Cochran formula. The data analysis technique used is multiple regression analysis using the SPSS program. The results of the study based on multiple regression analysis showed that the variables of sense, feel, think and act had a significant effect on the interest of tourists visiting Mandeh Island tourism object.